Six Arguments for Vygotskian Pragmatism in Deaf Education: Multimodal Multilingualism as Applied Harm Reduction. - Scott, Jessica; Henner, Jon; Skyer, Michael E. (American Annals of the Deaf)
Deaf education research and practice have not always lived up to the ideal of improving deaf students' lives. Consequently, we have constructed novel arguments supporting deaf pedagogy using pragmatic ethics, the aim of which is to increase benefit and decrease harm to individuals and society. The ideal of harm reduction asks the pragmatist to pursue the path of action least likely to result in injury to others. Besides applying ideas that reduce harm, educators must also increase benefits for deaf students. Our analysis synthesizes Vygotskian perspectives on deaf pedagogy and pragmatic ideals about reducing harm and increasing benefit. We propose six arguments that can enable deaf educators to think about and enact deaf-positive concepts and strengths-based classroom interactions, including the use of sign language, images, and text, among other modes, such as speech. Our goal is to reduce the threat of harm from language deprivation.